Conflict Triggers of KPTS Policy and Poverty Reduction using the Mopohulinta Approach - Harson Towalu (West Science Social and Humanities Studies, 2024)
This research focuses on analyzing indicators that can have a significant impact on employee performance in the organizational environment of PT Idea Indonesia Tbk. The main focus involves several aspects such as work environment, work motivation, and management support as key elements that play an important role in shaping and influencing employee productivity. This study uses quantitative methods to determine how much influence the variable (X), namely performance indicators and variable (Y), namely company employees at PT Idea Indonesia Tbk. The data obtained was analyzed with multiple linear regression tests. As such, this study aims to provide a comprehensive overview of the dynamics involved in improving employee performance. The results of research on performance indicators on employees have an F-test obtained F count of 3, 540 which states that all variables significantly affect the dependent variable (employee).